The prevalence of pulmonary hypertension after successful tuberculosis treatment in a community sample of adult patients. (19th January 2023) - Louw, Elizabeth; Baines, Nicola; Maarman, Gerald; Osman, Muhammad; Sigwadhi, Lovemore; Irusen, Elvis; Koegelenberg, Coenraad; Doubell, Anton; Nathan, Steven; Channick, Richard; Allwood, Brian
Abstract: There are an estimated 155 million survivors of tuberculosis (TB). Clinical experience suggests that post tuberculosis lung disease (PTLD) is an important cause of Group 3 pulmonary hypertension (PH). However, TB is not listed as a cause of PH in most guidelines. A cross‐sectional, community‐based study was conducted in nonhealthcare seeking adults who had successfully completed TB treatment. Subjects underwent questionnaires, spirometry, a 6‐min walk distance test (6MWD) and transthoracic echocardiography (TTE). Screen probable PH was defined on TTE as an estimated pulmonary artery peak systolic pressure (PASP) of ≥40 mmHg. One hundred adults (71 males) were enrolled, with a mean age of 42 years ( SD 13.8 years) and a median of one TB episode (interquartile range: 1–2). Co‐morbidities included hypertension (21%), diabetes (16%), human immunodeficiency virus (10%) and asthma/COPD (5%). Only 25% had no residual symptoms after TB. Probable PH was found in 9%, while 7% had borderline raised PASP values (PASP 35–40 mmHg). An association was found between PH and the number of previous TB episodes, with each additional episode of TB increasing the odds of PH‐postTB 2.13‐fold (confidence interval [CI]: 1.17–3.88; p  = 0.013). All of those found to have PH were smokers or ex‐smokers yielding an unadjusted odds ratio for PH‐postTB of 3.67 (95% CI: 0.77–17.46). There was no statistical difference in spirometry or 6MWD, between those with and without PH. Neither symptoms nor co‐morbidities demonstrated significant association with PH. PH after TB was a common finding in this community‐based population. Further research is needed to confirm and determine the significance of these findings.